Development of a Competitive and Adaptive Hindu Education Model in the Global Era by Integrating Local Wisdom Values and Modern Education - Astawa, I Putu Putra; Wimba, I Gusti Ayu; Apsari dewi, Komang Indra (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
Education is pivotal in preparing the younger generation to face global challenges. In this context, developing a competitive and adaptive Hindu education model becomes crucial, as it addresses the need to preserve cultural heritage while equipping students with the necessary skills to thrive in a globalized world. This research aims to integrate the values of local Hindu wisdom with modern education to create a relevant and effective system for nurturing well-rounded individuals. Using a mixed-methods approach, the study combines qualitative data from interviews with educators and community leaders with quantitative data gathered from surveys of students and teachers. These data sources are analyzed using thematic analysis and statistical tools to identify key local wisdom values and evaluate their integration into education. The findings indicate that incorporating local wisdom values into education strengthens cultural identity, fosters positive character development, and enhances student academic achievement. Instruments include interview guides and survey questionnaires, validated through expert review and pilot testing. However, this study is limited to specific regions, and further research is needed to test the model's applicability in diverse settings. The educational model developed in this study emphasizes the balance between character development, skills, and knowledge, producing graduates who are academically competent and culturally grounded. By bridging tradition and modernity, Hindu education can preserve local wisdom while preparing the younger generation to face global challenges.